Localization is Self-Determination - Slim, Hugo (Frontiers in Political Science, 2021)
This paper gives a personal political perspective on the policy dispute about localization in the humanitarian sector to argue that localization is a realization of the political right to self-determination. It starts by describing how humanitarian aid is too international today. It then makes the case for localization as an essential process of self-determination and humanitarian citizenship. It then analyses the main political arguments used against localization by international humanitarians who are resistant to it and shows how they routinely exaggerate the necessity of international aid by misrepresenting the reality of most humanitarian operations. Finally, the paper makes three recommendations to help humanitarian reform move forwards to find a fairer balance of local, national and international organizations.